2013
DOI: 10.7235/hort.2013.13049
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mist Treatment on the Growth and Quality of Cut Rose 'Hanmaum' during Summer

Abstract: Abstract. During summer in Korea, the excessively high temperature causes growth retardation and quality reduction in cut roses grown in greenhouse. Mist treatments were conducted to reduce the temperature and avoid quality reduction of cut roses. The temperature change in the greenhouse, growth and quality of cut roses, and injuries caused by insects or fungi were investigated during mist treatment. Daily maximum temperature reduced as the number of mist treatment increased, resulting in 6°C reduction by mist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…Similarly, our results showed that 2% PA irrespective of NPK fertilizer rate increased the total number of fruits and fruit weight followed by 0.5% PA combined with full NPK rate. Although the positive effect of NPK cannot be neglected, a similar increase in fruit number and weight have been reported in tomato 19,20,23 and sweet pepper (Capsicum annuum) 47 . Although the exact mechanism of the PA-mediated increase in fruit yield is still under investigation, it can be suggested that the increase in fruit yield could be due to increased chlorophyll content which indicates high photosynthetic translocation of assimilates into the increased number of fruits 42,48 .…”
Section: Discussionsupporting
confidence: 66%
“…Similarly, our results showed that 2% PA irrespective of NPK fertilizer rate increased the total number of fruits and fruit weight followed by 0.5% PA combined with full NPK rate. Although the positive effect of NPK cannot be neglected, a similar increase in fruit number and weight have been reported in tomato 19,20,23 and sweet pepper (Capsicum annuum) 47 . Although the exact mechanism of the PA-mediated increase in fruit yield is still under investigation, it can be suggested that the increase in fruit yield could be due to increased chlorophyll content which indicates high photosynthetic translocation of assimilates into the increased number of fruits 42,48 .…”
Section: Discussionsupporting
confidence: 66%
“…Each species and, in many cases, each variety has specific requirements. In the case of temperature, Chon et al (2013), report that plant height and fresh weight of roses under greenhouse misting increased in the range of 10-20%, although these conditions increased the number of malformed flowers and decreased the vase life. On the other hand, Katsutani and Ikeda (1997), found an acceleration of the process of flower bud differentiation and improved seedling formation when the temperature was above 20 °C.…”
Section: Crop Managementmentioning
confidence: 99%
“…In particular, mist is often used in high PM episodes because it can reduce PM by condensing PM growth (Kyung, 2018), mitigating PM damage to trees. Additionally, spraying mist may reduce temperature and increase relative humidity, preventing dry heat damage to trees and enhancing tree functions such as PM reduction (Nam et al, 2005;Chon et al, 2013).…”
Section: Introductionmentioning
confidence: 99%